2022
DOI: 10.1172/jci158593
|View full text |Cite
|
Sign up to set email alerts
|

CDK8 and CDK19 regulate intestinal differentiation and homeostasis via the chromatin remodeling complex SWI/SNF

Abstract: Initiation and maintenance of transcriptional states are critical for controlling normal tissue homeostasis and differentiation. Cyclin Dependent Kinases CDK8/CDK19 (Mediator kinase) are regulatory components of Mediator, a highly conserved complex that orchestrates enhancer-mediated transcriptional output. While Mediator kinase has been implicated in the transcription of genes necessary for development and growth, its function in mammals has not been well defined. Using genetically defined models and pharmaco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 64 publications
3
9
0
Order By: Relevance
“…Paneth cell, goblet and tuft cell counts were decreased, while the number of absorptive cells significantly increased. It was shown that CDK8 and CDK19 allowed secretory lineage differentiation by upregulating Atoh1 expression with an ARID1A-defined enhancer upon interaction with SWI/SNF [70]. Thus, this model confirms that the Mediator functions are not limited to transcription modulation, but take part in chromatin remodeling.…”
Section: Intestinal Knockoutsupporting
confidence: 60%
“…Paneth cell, goblet and tuft cell counts were decreased, while the number of absorptive cells significantly increased. It was shown that CDK8 and CDK19 allowed secretory lineage differentiation by upregulating Atoh1 expression with an ARID1A-defined enhancer upon interaction with SWI/SNF [70]. Thus, this model confirms that the Mediator functions are not limited to transcription modulation, but take part in chromatin remodeling.…”
Section: Intestinal Knockoutsupporting
confidence: 60%
“…Indeed, there are 95 solute carriers whose expression is deregulated in CDK8/19 knockouts (Table EV2), including four inorganic anion transporters of the Slc26 family, all of which are upregulated, and which might contribute to the phenotype. While this study was still ongoing, a report was published in which, using a similar genetic approach in mice and intestinal organoids, CDK8 and CDK19 were found to be dispensable for intestinal morphology and viability but were observed to redundantly control intestinal lineage specification (Dannappel et al, 2022). In particular, a decrease in number of paneth cells, tuft cells, and goblet cells were reported in intestinal tissue lacking both kinases, a result that we do not reproduce.…”
Section: Discussionmentioning
confidence: 72%
“…If CDK8 and CDK19 functions are redundant, DKO would show a phenotype that is not produced by the knockout of Cdk8 or Cdk19 alone. Previously described animals with conditional knockout of Cdk8 in the intestine on Cdk19 -/- background presented with a mild phenotype, moderately affecting the number of specialized secreting cells (Dannappel et al 2022). At the same time, our DKO mice had a phenotype evident at the histological level: they lacked haploid spermatids and mature spermatozoa (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, conditional Cdk8 KO is almost asymptomatic in adult mice, and the lifespan is normal. Minor differences were observed in colon epithelial differentiation [12,13] and tumorigenesis [14] as well as in osteoclastogenesis [15] after tissue specific Cdk8 knockout.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation